IoT AND BLOCKCHAIN IN HORTICULTURE CROP SUPPLY CHAIN (CAHIERS MAGELLANES-NS, 2024)
Food consumption is necessary for a healthy lifestyle, and natural resource preservation is critical. As a result, technical approaches must be employed to maintain and strengthen natural resource bases while also boosting production proportion to the population. IoT and blockchain are playing an increasingly important role in agriculture. From the beginning, with the fundamental premise of providing data security from planting crops, irrigation, and harvesting to the food supply, allowing people to manage the life cycle of their crops better and prevent the risk of bad quality. Agriculture and its supply chain are two significant areas of research that need to be addressed if rising countries like India are to flourish where food safety and supply chain management are gaining global attention concerning health issues. This innovative agricultural approach aids in collecting environmental data, such as weather crisis control, reduced landholding size, with the majority of land being terrains and inclination hills, and gaining a better understanding of expenses through direct interaction with retailers.